Anaphylaxis and onsite treatment in schools, kindergartens, and nurseries. Issue 1 (21st March 2022) - Korematsu, Seigo; Kaku, Minako; Kitada, Shun; Etoh, Mie; Kai, Hiroko; Joh, Miho; Nakano, Kazue; Nakamura, Midori; Sato, Kensho; Wakita, Yoshiyuki; Matsumoto, Shigetaka; Yada, Kimihiro; et al.
Abstract: Background: There have been no reports on both anaphylaxis incidence rate in schools, kindergarten, and nurseries, or how teachers have treated these children. This study was a fact‐finding survey aimed at determining if appropriate responses to anaphylaxis onset were implemented in Oita Prefecture, Japan. Methods: The Oita Prefectural Allergy Control Committee administered a questionnaire using Google forms to all public and private schools, public and private kindergartens, certified child‐care facilities, and day‐care centers in the prefecture. Results: Responses to the questionnaire were obtained from 597 institutions, of which 125 890 children were affiliated with the responding institutions. Forty‐eight children developed symptoms for which an adrenaline auto‐injector was recommended in an Oita guideline. Among these children, three used the adrenaline auto‐injector, three were prescribed the adrenaline auto‐injector but were unable to use it, 27 were unable to use it as they were not prescribed an adrenaline auto‐injector, and the final 15 responded that they handled their symptoms via another method because none of the above options apply. Conclusions: Most children who developed symptoms which an adrenaline auto‐injector was recommended had no prescription for an adrenaline auto‐injector. There is thus a need for appropriate response training to anaphylaxis whether or not an adrenaline auto‐injector was prescribed.